2007
DOI: 10.1111/j.1365-2648.2007.04111.x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and ‘stress of conscience’ among healthcare personnel

Abstract: Title. Burnout and 'stress of conscience' among healthcare personnel Aim. This paper reports a study examining factors that may contribute to burnout among healthcare personnel. Background. The impact on burnout of factors such as workload and interpersonal conflicts is well-documented. However, although health care is a moral endeavour, little is known about the impact of moral strain. Interviews reveal that healthcare personnel experience a troubled conscience when they feel that they cannot provide the good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
247
4
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(277 citation statements)
references
References 55 publications
16
247
4
10
Order By: Relevance
“…The results showed that the physicians in specialization training perceived many functions of social support in their work. Considering earlier studies [1113,18,19], it is not surprising that the stress-management function strongly emerged in the data. In several earlier studies, a covariation was revealed between physicians’ coping skills and social support [612]; this connection was recognized by the physicians in training as well.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The results showed that the physicians in specialization training perceived many functions of social support in their work. Considering earlier studies [1113,18,19], it is not surprising that the stress-management function strongly emerged in the data. In several earlier studies, a covariation was revealed between physicians’ coping skills and social support [612]; this connection was recognized by the physicians in training as well.…”
Section: Discussionmentioning
confidence: 76%
“…It can prevent psychiatric symptoms and common mental disorders [14,15] and has a protective function against possible suicidal intentions [16,17]. Low social support from co-workers is associated with emotional exhaustion [18,19]. Interestingly, when there are low co-worker support and limited possibilities to control one’s job, physicians are more likely to experience poor psychological well-being than other healthcare professionals [20].…”
Section: Introductionmentioning
confidence: 99%
“…Work overload and exhaustion are 2 such impediments and are well-recognized contributors to burnout. 9,12 Incongruence of values, as studied by Leiter et al, 13,14 and moral strain, as studied by Glasberg et al, 15 are other means or pathways to burnout that are less well recognized. These occur when health care professionals sense a lack of alignment between their own values and those they perceive to be the values of various health care-related organizations or groups with which they are associated.…”
Section: Ethics and Values In Clinical Practice: Whom Do They Help?mentioning
confidence: 99%
“…Glasberg et al 15 have emphasized that health care is a moral undertaking. Health care professionals they have studied experience "[a] troubled conscience when they feel that they cannot provide the good care they wish-and believe is their duty-to give."…”
Section: Ethics and Values In Clinical Practice: Whom Do They Help?mentioning
confidence: 99%
See 1 more Smart Citation